Answer:
y =
-
![(1)/(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ykdkxxvb0vy4uekf2qgigigcflq5pi94b6.png)
Explanation:
The line (l1) passes through (-2, 1) and is perpendicular to the line whose equation is;
3x - 2y = 5
Converting this equation to slope intercept form gives;
2y = 3x - 5
y = 1.5x - 2.5
Let the slope of the perpendicular line (l2) be m(PERP).
The product of slopes of two perpendicular lines is -1
The slope of our first line (l1) = 1.5
So 1.5 × m(PERP) = -1
m(PERP) = -1 ÷ 1.5 =
![-(2)/(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/9b735wr1uu4p8fxc1vii1igfgpgrg7hpoy.png)
Taking another point (x,y) on line (l2);
![(y - 1)/(x + 2) = -(2)/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/im7yocalfzn3lbd6zacp879s1qav1tc7x9.png)
Cross multiplying this gives;
y =
-
![(1)/(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ykdkxxvb0vy4uekf2qgigigcflq5pi94b6.png)
which is the equation of our second line (l2).